A Qualitative Study of Patient Protection against Postoperative Opioid Addiction: A Thematic Analysis of Self-Agency. Issue 5 (27th April 2021) - Cho, Hoyune E.; Billig, Jessica I.; Byrnes, Mary E.; Nasser, Jacob S.; Kocheril, Alex P.; Haase, Steven C.; Waljee, Jennifer F.; Chung, Kevin C.
Abstract : Background: Opioids are commonly used following outpatient surgery. However, we understand little about patients' perspectives and how patients decide on postoperative opioid use. This study seeks to investigate aspects of patients' thought processes that most impact their decisions. Methods: The authors conducted semistructured interviews with 30 adults undergoing minor elective hand surgery at one tertiary hospital. Narratives were content-coded to arrive at the authors' thematic analysis. The authors incorporated Bandura's concept of self-agency to interpret the data and develop a conceptual framework that best explained the implicit theory within participants' responses. Results: The authors found six themes under two domains of self-agency. Participants actively sought out protective mechanisms supporting their decision on opioid use, but sometimes did so unconsciously. They would avoid opioids postoperatively because they were "tough" and wanted to evade the risk of addiction as "good citizens." They conveyed a nuanced safety against addiction because they were "not the kind" to become addicted and because they trusted the surgeons' prescribing. However, participants felt discouraged by the stigma associated with opioids. Both intentionally and unintentionally, participants integrated a strong sense of self in their decision-making processes. Conclusions: A robust understanding of how patients choose to take opioids for postoperative pain control is imperative to develop patient-centered strategies to treat the opioid epidemic. Effective opioid-reduction policies should consider patients as active agents who negotiate various internal and external influences in their decision-making processes. Surgeons must incorporate patients' individual goals and perspectives regarding postoperative opioid use to minimize opioid-related harm after surgery.